Drivers and Directions of Academic Library Development 2005 - Cotta-Schönberg, Michael (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
The purpose of this paper is not to guess what the future of academic libraries will be, but to identify and understand the present driving forces with a view to choosing and influencing directions of development, which will be advantageous to our users. Four major players will be considered: the ICT-industry, the academic institutions, the publishing industry, and the libraries.